Aquaponics as a Promising Strategy to Mitigate Impacts of Climate Change on Rainbow Trout Culture - Christos Vasdravanidis; Maria V. Alvanou; Athanasios Lattos; Dimitrios K. Papadopoulos; Ioanna Chatzigeorgiou; Maria Ravani; Georgios Liantas; Ioannis Georgoulis; Konstantinos Feidantsis; Georgios K. Ntinas; Ioannis A. Giantsis (Animals, 2022)
The impact of climate change on both terrestrial and aquatic ecosystems tends to become more progressively pronounced and devastating over the years. The sector of aquaculture is severely affected by natural abiotic factors, on account of climate change, that lead to various undesirable phenomena, including aquatic species mortalities and decreased productivity owing to oxidative and thermal stress of the reared organisms. Novel innovative technologies, such as aquaponics that are based on the co-cultivation of freshwater fish with plants in a sustainable manner under the context of controlled abiotic factors, represent a promising tool for mitigating the effect of climate change on reared fish. The rainbow trout (Oncorhynchus mykiss) constitutes one of the major freshwater-reared fish species, contributing to the national economies of numerous countries, and more specifically, to regional development, supporting mountainous areas of low productivity. However, it is highly vulnerable to climate change effects, mainly due to the concrete raceways, in which it is reared, that are constructed on the flow-through of rivers and are, therefore, dependent on water’s physical properties. The current review study evaluates the suitability, progress, and challenges of developing innovative and sustainable aquaponic systems to rear rainbow trout in combination with the cultivation of plants. Although not commercially developed to a great extent yet, research has shown that the rainbow trout is a valuable experimental model for aquaponics that may be also commercially exploited in the future. In particular, abiotic factors required in rainbow trout farming along, with the high protein proportion required in the ratios due to the strict carnivorous feeding behavior, result in high nitrate production that can be utilized by plants as a source of nitrogen in an aquaponic system. Intensive farming of rainbow trout in aquaponic systems can be controlled using digital monitoring of the system parameters, mitigating the obstacles originating from extreme temperature fluctuations.